O poder de punir o outro e o sentido do castigo provisório: atuações, textos e discursos em câmaras criminais do TJRS - Rizzardi, Paulo Renato Ardenghi (2012)
This research sets out to analyze the criminal legal field, using as a central object of study the distinct constituent dimensions of sentences pronounced in two criminal chambers of the Court of Justice of Rio Grande do Sul, referring to the granting of the order of Habeas Corpus or maintenance of the preventive custody of the defendant. Understanding the process of construction of the sentences, inserted in a social context consisting of symbolic, cultural, subjective, valuable elements and by the multiplicity of existing meanings in the rituals of judgment and punishment of the transgressor, there is a need to extend the epistemological bases beyond the regulatory analysis and to proceed to an ethnographic study of the functioning and the relations that take place within the legal field. It is assumed that the legal constructions express values, retrace ideologies and constitute a field of intense struggles for conditions to say and decide for the right. It is used as a source of research the participant observation in hearings of two criminal chambers of the TJRS, the documentary analysis of decisions pronounced in the respective chambers, as well as the conduction of semi-structured interviews with magistrates. The analysis of the fight between agents and institutions for the monopoly of the legitimated violence, or either, the power to impose symbolically when and how the State can punish the other provisionally will occupy a relevant space in this study.